Implikasi Pan-Islamisme Jamaluddin Al-Afghani terhadap Pembaruan Pendidikan Islam - Zulfa Khairiah Ali; Iefone Shiflana Habiba; Maragustam Siregar (Akhlak : Jurnal Pendidikan Agama Islam dan Filsafat, 2026)
The notion of Pan-Islamism articulated by Jamaluddin al-Afghani in the latter half of the nineteenth century is commonly read as a political response to European colonial expansion into the Muslim world, while its pedagogical dimension remains under-examined. This article analyzes the conceptual implications of al-Afghani's Pan-Islamism for the reform of Islamic education at the philosophical, institutional, and curricular levels. Employing a qualitative library-research method with a historical-analytical approach, this study examines al-Afghani's primary writings and correspondence alongside recent secondary scholarship. The findings indicate that al-Afghani's Pan-Islamism is inseparable from an educational project demanding three fundamental shifts: deconstructing the dichotomy between religious and secular knowledge through the reopening of ijtihad; reorienting educational epistemology from rote-dogmatic learning toward rational-critical reasoning; and cultivating a consciousness of communal solidarity (ukhuwah islamiyah) as the basis for a transnational civic curriculum. These ideas found institutional expression in reformist educational establishments across Egypt, Turkey, India, and the Dutch East Indies. The study also identifies an inherent tension between al-Afghani's rational-modernist orientation and his solidarity rhetoric, which carries a risk of exclusivist misreading. It concludes that the relevance of Pan-Islamism for contemporary Islamic education lies not in the romanticism of political unity but in its ethos of open, critical, and adaptive epistemic reform.